Perhitungan Poros Roda Depan Motor Honda Vario 110 tipe CW - Muhammad Nur Yasin; Reza Setiawan; Najmudin Fauji (Peneliti.net, 2022)
The shaft is one component of a motorcycle that is no less important than other components. These components function to support the load of the vehicle itself as well as external loads such as humans or cargo on a motorcycle.This study aims to determine the working stress and also the safety factor on the shaft.The component that will be discussed is the front axle of the Honda Vario 110 tipe CW motorcycle.The method used is an experimental method with qualitative and quantitative analysis.The results of the analysis show that if a load of 80 kg is given, then the value of the working stress is 163,28 N/mm2, while the safety factor is 2.1.